বিশ্বসাহিত্য কেন্দ্র ও আমি - সায়ীদ, আব্দুল্লাহ আবু (ঢাকা : মাওলা ব্রাদার্স, 2007)
Articles chiefly on Bishwasahitya Kendra, a literary forum of international scope, located at Dhaka, Bangladesh; includes interviews with its founder, the author.
In Bengali.
Keywords: Literature -- Societies, etc; Bishwasahitya Kendra (Dhaka, Bangladesh); Sayeed, Abdullah Abu -- Interviews